IRDAI'S ROLE IN CONSUMER PROTECTION IN THE INSURANCE SECTOR (International Journal of Food and Nutritional Sciences, 2022)
The Insurance Regulatory and Development Authority of India (IRDAI) plays a crucial role in safeguarding consumer interests within the insurance sector. Established in 1999, IRDAI's primary mandate is to regulate and promote the growth of the insurance industry while ensuring the protection of policyholders. As the insurance market expanded, especially with the entry of private and foreign players post-1991, the need for a robust regulatory framework became evident to prevent exploitation, fraud, and mis-selling. IRDAI’s role in consumer protection is multifaceted. It ensures transparency by regulating the design and marketing of insurance products, making sure that they are clear, fair, and meet the needs of diverse consumer segments. The authority enforces stringent guidelines that require insurers to provide clear, accessible policy documents that outline benefits, exclusions, and terms of coverage.